A STUDY ON ANTIMICROBIAL ACTIVITY OF EXTRACTS OF LUFFA ACUTANGULA VAR AMARA FRUITS - JANAKI R. TORVI; RAJESH D. HUNASHAL (International Journal of Pharma and Bio Sciences, 2012)
The present study involves extraction, phytochemical investigation and in-vitro antimicrobial activity of Luffa acutangula var amara fruits known as Kadwi turai in Hindi. The phytochemical investigation revealed the presence of sterols and glycoside in chloroform extract. The chloroform extract showed significant antimicrobial activity than aqueous extract. Both extracts showed weak antifungal activities.